1988
DOI: 10.1104/pp.88.3.947
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Nitrogen-Assimilating Enzymes in the Chloroplast of Chlamydomonas reinhardtii

Abstract: The specific activities of nitrate reductase, nitrite reductase, glutamine synthetase, glutamate synthase, and glutamate dehydrogenase were determined in intact protoplasts and intact chloroplasts from Chlamydomonas reinhardtii. After correction for contamination, the data were used to calculate the portion of each enzyme in the algal chloroplast. The chloroplast of C. reinhardtii contained all enzyme activities for nitrogen assimilation, except nitrate reductase, which could not be detected in this organelle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 38 publications
3
32
1
2
Order By: Relevance
“…1). This indicates that in C. reinhardtii the three NAD(P)'-GDH isozymes are located in mitochondria, in contrast to their localization in chloroplasts described by Fischer and Klein (4). This localization of NAD(P)'-GDH in mitochondria is consistent with the elevation of total GDH When cells of C reinhardtii 6145c phototrophically grown with 10 mm NH4Cl were kept in the dark in the presence of cycloheximide, an inhibitor of protein synthesis in cytosolic 80S ribosomes (5, 13), GDH1 and GDH2 synthesis was prevented ( Fig.…”
Section: Isolation and Purification Of Mitochondria From C Reinhardtiicontrasting
confidence: 50%
See 1 more Smart Citation
“…1). This indicates that in C. reinhardtii the three NAD(P)'-GDH isozymes are located in mitochondria, in contrast to their localization in chloroplasts described by Fischer and Klein (4). This localization of NAD(P)'-GDH in mitochondria is consistent with the elevation of total GDH When cells of C reinhardtii 6145c phototrophically grown with 10 mm NH4Cl were kept in the dark in the presence of cycloheximide, an inhibitor of protein synthesis in cytosolic 80S ribosomes (5, 13), GDH1 and GDH2 synthesis was prevented ( Fig.…”
Section: Isolation and Purification Of Mitochondria From C Reinhardtiicontrasting
confidence: 50%
“…These authors isolated chloroplasts from Chlamydomonas cells kept under dark conditions during 9 h, after which time a higher yield of chloroplasts than in the light was found. In chloroplasts, GDH may be involved in protein degradation or amino acid turnover (2), but its physiological role is still not completely understood (4). In C reinhardtii 6145c, we found that total GDH activity was strongly induced under dark conditions (16).…”
Section: Resultsmentioning
confidence: 60%
“…They were then incubated at 4°C for 40 min. After adding 3 mL H20 the samples were centrifuged and the upper aqueous phase dried (10 (40). The PFP used in the assay of Fru-2,6-P2 was partially purified (235-fold) from 1 kg of potato (Solanum tuberosum) tubers, using a P-lI Cellulose Phosphate column (Whatman) and a Q-Sepharose (1 x 6.5 cm) column (Pharmacia) (44).…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…The localization of GDH in higher plant and algal chloroplasts has also been reported (7,19,27). In one study, the subunit-precursor of chloroplastic GDH was shown to be synthesized in the cytosol (19).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, GDH was found to be localized exclusively in the chloroplast of Chiamydomonas, and the enzyme was shown to be equally active with NAD and NADP (7). An ammonium inducible NADP-GDH was also reported to be located in the chloroplasts of Chlorella, however, its subunit-precursor was shown to be synthesized in the cytosol ( 19).…”
mentioning
confidence: 99%